Once more on musical topics and style analysis. A critical examination of Agawu’s analysis of the introduction to Beethoven’s Pathetic Sonata - Ana Stefanovic (Zeitschrift der Gesellschaft für Musiktheorie)
The article begins with the analysis of the introduction to Beethoven’s Pathétique Sonata as presented in Playing with Signs by Kofi Agawu, with the intention of posing several questions concerning meaning and function of musical “topics.” In this context, attention is drawn to terminological ambiguities, i.e. to ambiguities in defining the concept of topics, especially in view of similarities and differences with the concept of topos. Subsequently, the question may be asked, “What constitutes a musical topic/topos?” If it is supposed that it represents a sign-function (Umberto Eco), what is a minimal entity that is sufficient to be referred to as a topic/topos? Consequently, what kind of relations does it establish towards style, which still shows itself to be the main referential plane (the content) of topical expression? Finally, the question arises of whether an ‘atomistic’, taxonomic approach to musical “topics” denies – contrary to the intentions of the authors using this term – the semantic aspect of music in which the topics ‘may be found,’ reducing it to the ‘play’ of formal elements, i.e. to purely ornamental function of rhetorical locus communis. Should the place of topic/topos perhaps be looked for elsewhere, in the plane of discourse and narrative structure of the musical text?